Perancangan Ikon Visual Dusun Plosokerep Melalui Pengembangan Motif Batik Daun Ploso sebagai Identitas Komunal - Ninggar Mayang Ningrum; Avierry Fionarizoca; Abdurrozaq (Redtech Putra Benua, 2026)
The community of Plosokerep Hamlet, Gondangrejo, Karanganyar, possesses a rich tradition of local performing arts but lacks a cohesive visual identity in the form of a signature village batik motif for ceremonial attire. This Community Service Program (PkM) aims to assist the community in designing a local visual icon based on native flora—specifically the leaves of the ploso tree (Butea monosperma)—leading to the creation of the